2023
DOI: 10.3390/ani13061041
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic Acid Supplementation during the In Vitro Culture Period Ameliorates Early Embryonic Development of Porcine Embryos by Regulating Oxidative Stress

Abstract: As a pentacyclic triterpene, MA exhibits effective free radical scavenging capabilities. The purpose of this study was to explore the effects of MA on porcine early-stage embryonic development, oxidation resistance and mitochondrial function. Our results showed that 1 μM was the optimal concentration of MA, which resulted in dramatically increased blastocyst formation rates and improvement of blastocyst quality of in vitro-derived embryos from parthenogenetic activation (PA) and somatic cell nuclear transfer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…Mitochondrial membrane potential is generally used as a marker of mitochondrial function in embryos (Hu et al., 2021). Our results are consistent with those of a previous study showing that an increase in mitochondrial membrane potential can improve mitochondrial function, thereby enhancing embryonic development potential (Yang et al., 2023). We also found that CGA significantly upregulated the expression of the mitochondrial biogenesis‐related gene NRF‐1 in porcine PA early‐stage embryos.…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondrial membrane potential is generally used as a marker of mitochondrial function in embryos (Hu et al., 2021). Our results are consistent with those of a previous study showing that an increase in mitochondrial membrane potential can improve mitochondrial function, thereby enhancing embryonic development potential (Yang et al., 2023). We also found that CGA significantly upregulated the expression of the mitochondrial biogenesis‐related gene NRF‐1 in porcine PA early‐stage embryos.…”
Section: Discussionsupporting
confidence: 93%